Indirect carotid-cavernous fistula following minor head trauma treated with incomplete radiographic endovascular occlusion. (24th September 2012) - Stetler, William R; Chaudhary, Neeraj; Wilson, Thomas J; Pandey, Aditya S
Abstract : We report the unusual case of a patient with an indirect carotid-cavernous fistula treated with only partial angiographic embolisation of the fistula; however, by 8 weeks postembolisation, she was found to have both symptomatic and angiographic cure. This case highlights the potential for treating indirect carotid-cavernous fistulas with partial embolisation as a means of achieving angiographic and symptomatic cure by altering flow dynamics to attain spontaneous thrombosis.